Peningkatan Kemampuan Kewirausahaan Ibu-ibu Rumah Tangga Di RW 18 Kalurahan Baciro Kota Yogyakarta Melalui Pembuatan Ecoprint - Winarna, Winarna; Probo Saputra, Kuncoro; Seliari, Tutun; Hartono, Steffany (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
The high poverty rate in DIY requires efforts to increase people's income. Some things that need to be done are creating jobs for people in the lower classes, increasing farmers' income, and increasing the income of small businesses. Poverty alleviation programs need to be held by the conditions of the target community and their environment. Based on the monographic data obtained, it is known that the majority of residents in RW 18, Baciro Subdistrict, make their living as laborers and small traders, MSMEs in RW 18, Baciro Subdistrict are still not developed, homemakers in RW 18, Baciro Subdistrict are still unemployed, and less productive. Most homemakers need help generating income to help with household finances. For this reason, activities are needed to empower the community, especially homemakers, to earn income to meet family needs. Homemakers need to be encouraged to be more creative by making products that have economic value. This community service activity aims to improve the entrepreneurial abilities of homemakers in RW 18 Baciro Village. Service activities are carried out in the form of counseling about the importance of developing skills in the field of entrepreneurship, followed by training on how to make Ecoprints that are economically valuable. Furthermore, in the third stage, digital content creation and online marketing training were carried out to support promoting and marketing eco-print products. As a result of this PKM activity, homemakers in RW18, Baciro Village, Gondokusuman District, Yogyakarta, know and understand the importance and benefits of entrepreneurship and have skills in making economically valuable eco prints. However, forming an ecoprint business group and entrepreneurship counseling activities are still needed Intense.